Perancangan Continuous Barge Unloader Kapasitas 800 Ton/Jam Bermuatan Batu Bara - Satria, Dhimas; Aswata, Aswata; Listijorini, Emy; Rosyadi, Imron; Haryadi, Haryadi; Lusiani, Rina; Irsyadi, Muhammad Furi (MECHANICAL ; Jurnal Ilmiah Teknik Mesin, 2017)
It is undeniable energy needs in Indonesia is increasing, and can never be separated from the need to use material of coal as a source of energy. So that industry has a role in the processing of coal should be increased productivity. One is an increase in productivity of the use of coal loading and unloading equipment at ports which handle ships - collier. This final project offers an example of the calculation and planning of loading and unloading equipment Continuous Barge Unloader capacity of 800 tons / hour for barges loaded with coal which is normally used in the industry, especially coal handling plant. The final project is expected to be the solution for the lack of productivity of the loading and unloading of coal and one of the reference design tool manufacture Continuous Barge Unloader. This design uses Pahl and Beitz method and the results of this research in the form of structural design tools, the selection of the main component unloader (driving, lifting, belt conveyor, bucket conveyor, and electric motors for lifting and driving).